Concurrence of Sweet's Syndrome, Pathergy Phenomenon and Erythema Nodosum-like Lesions - Jianjun Qiao; Yan Wang; Juan Bai; Yinhua Wu; Hong Fang (Sociedade Brasileira de Dermatologia, 2015)
We report the case of a 54-year-old woman with concurrent Sweet's syndrome, pathergy phenomenon and eythema nodosum-like lesions associated with suppurative tonsillitis. Tender, violaceous and highly edematous papules and plaques were detected on the forearms and legs, some of which were pseudovesicular. Similar edematous papules were detected on the dorsum of the hands at the sites of intravenous injection. Biopsies of a plaque on the forearm and a papule at the site of intravenous injection confirmed the presence of Sweet's syndrome. Multiple, tender, violet-red, subcutaneous erythematous nodules were revealed on the legs. A biopsy taken from a nodule on the leg revealed septal panniculitis. To our knowledge, no patient with concurrent Sweet's syndrome, pathergy phenomenon, and erythema nodosum-lesions had been reported yet in previous literature.